Feminist international relations : an unfinished journey - Sylvester, Christine, 1949- (Cambridge, U.K. ; New York : Cambridge University Press, 2002)
Christine Sylvester examines the history of feminists' efforts to include gender relations in the study of international relations. Tracing the author's own 'journey' through the subject, the book examines theories, methods, people and locations which have been neglected by conventional scholarship.
Looking backwards and forwards at international relations around feminism -- Introducing Elshtain, Enloe, and Tickner: looking at key feminist efforts before journeying on -- Handmaids' tales of Washington power: the abject and the real Kennedy White House -- Reginas in international relations: occlusions, cooperations, and Zimbabwean cooperatives -- The white paper trailing -- Picturing the Cold War: an eye graft/art graft -- Four international Dianas: Andy's tribute -- The emperors' theories and transformations: looking at the field through feminist lenses -- Feminists and realists view autonomy and obligation in international relations -- Some dangers in merging feminist and peace projects -- Gendered development imaginaries: shall we dance, Pygmalion? -- Empathetic cooperation: a feminist method for IR -- Feminist arts of international relations -- Internations of feminism and international relations.
Includes bibliographical references (pages 317-345) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: International relations -- Philosophy; Feminist theory; Théorie féministe.; POLITICAL SCIENCE -- Globalization; Feminist theory; International relations -- Philosophy; Internationale betrekkingen; Feminisme; Relaciones internacionales -- Filosofía.; Teoría feminista; Electronic books; Electronic books